Stuck endotracheal tube in the trachea: An unusual case - Adhikari, Kiran; Prasad Deo, Gopendra (Journal of Chitwan Medical College, 2024)
Endotracheal (ET) intubation is one of the most commonly performed procedures by anaesthesiologists to provide ventilation and oxygenation during general anaesthesia. The techniques for intubation in difficult airways have been widely studied, and equipment is available to help with the same. However, less is known about the difficulties during extubation after surgery in otherwise healthy patients. Thus, only a few pieces of literature are available. We report a case of a stuck endotracheal tube in an 81 years old female, who underwent laparoscopic cholecystectomy. During laryngoscopy, modified Cormack-Lehane grade 1 was noted, however, only a 6.0 mm internal diameter tube could be inserted. The patient received optimum ventilation and oxygenation with no other complications intraoperatively. After full consciousness and adequate tidal volume were regained, an attempt to remove ET was unsuccessful as it was stuck in the trachea. The case reported previously mostly focuses on the laryngeal edema that occurred during intubation or the mechanical defects in the tube. In the present case a narrowed subglottic area, laryngeal edema, and a complete ring formation were found in the deflated ET tube cuff, which was stuck in the subglottic area. We report an unusual case of a stuck ET tube in an otherwise healthy elderly lady.